Increasing Of Aloe vera Products Performance At Women Farmer Group “Sri Rejeki”, Batu City - Mas’ud Effendi (Journal of Innovation and Applied Technology, 2015)
ABSTRACT Women Farmer Group "Sri Rejeki" was formed with the objectives to  empo-wer farmer communities Ngaglik Village, Batu.  They produce Aloe vera based products such as jelly candies, instant powder, jam, and syrup. The problem faced by this group is low production efficiency that impact on low quality and quantity of Aloe vera based products, that makes less competitiveness to gain larger market share.  This group  needs tech-nology transfer and innovation in order to produce higher quality products through LLM (Low Technology, Low Investment, and Marketable). By this program, the activities included dissemination of good manufacturing practices, standard ope-rating production (SOP) as well as the facilitation of production machines and equipment such as blender, mixer mechanical and oven for processed aloe vera based products. These equipments have been used and increase  production efficiency indicating by shorter production time, higher production capacity and higher product quality.Keywords: aloe vera, capacity, efficiency, production, technology transfer